2021
DOI: 10.1371/journal.pone.0250820
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes for a complete nationwide cohort of more than 3200 teriflunomide-treated multiple sclerosis patients in The Danish Multiple Sclerosis Registry

Abstract: Objective Teriflunomide is a once-daily, oral disease-modifying therapy (DMT) for relapsing forms of multiple sclerosis (MS). We studied clinical outcomes in a real-world setting involving a population-based large cohort of unselected patients enrolled in The Danish Multiple Sclerosis Registry (DMSR) who started teriflunomide treatment between 2013–2019. Methods This was a complete nationwide population-based cohort study with prospectively enrolled unselected cases. Demographic and disease-specific patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…22 A complete nationwide population-based cohort study conducted in 3239 patients who were treated with teriflunomide depicted that there was a higher percentage of patients in the treatment-naive group experienced relapse when compared to the patients who had been treated with teriflunomide (p < 0.0001). 23 The adverse events reported (n/N [%]) in the Kuwait cohort were hair thinning (6/52 [11.5%]), diarrhea (5/ 52 [9.6%]), headache (4/52 [7.7%]), increase in alanine transaminase (3/52 [5.8%]), nausea (4/52 [7.7%]), and skin rashes (2/52 [3.8%]) (Table 1). These safety results were comparable to the major clinical trials, namely Teriflunomide Phase II, TEMSO, TOWER, and TOPIC (Table 1).…”
Section: Kuwait Ms Cohort Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A complete nationwide population-based cohort study conducted in 3239 patients who were treated with teriflunomide depicted that there was a higher percentage of patients in the treatment-naive group experienced relapse when compared to the patients who had been treated with teriflunomide (p < 0.0001). 23 The adverse events reported (n/N [%]) in the Kuwait cohort were hair thinning (6/52 [11.5%]), diarrhea (5/ 52 [9.6%]), headache (4/52 [7.7%]), increase in alanine transaminase (3/52 [5.8%]), nausea (4/52 [7.7%]), and skin rashes (2/52 [3.8%]) (Table 1). These safety results were comparable to the major clinical trials, namely Teriflunomide Phase II, TEMSO, TOWER, and TOPIC (Table 1).…”
Section: Kuwait Ms Cohort Descriptionmentioning
confidence: 99%
“…22 A complete nationwide population-based cohort study conducted in 3239 patients who were treated with teriflunomide depicted that there was a higher percentage of patients in the treatment-naive group experienced relapse when compared to the patients who had been treated with teriflunomide ( p < 0.0001). 23…”
Section: Overview Of Clinical Trials and Case Studies From Gcc On Ter...mentioning
confidence: 99%
“…However, we think that our results can add relevant knowledge to the current understanding of teriflunomide effectiveness and safety in a real-world setting for several reasons: In contrast to an Italian survey, the TAURUS MS study was designed in a prospective way [ 20 ]. Furthermore, different recent studies did not include patient-related outcomes as an outcome parameter [ 20 , 22 ]. Nevertheless, despite the small sample size, the results support those of the German TAURUS MS I study, which showed a significant decrease in the mean ARR within 24 months of initiation of teriflunomide treatment, plus significantly improved patient satisfaction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the TERI-PRO study revealed significant improvements in treatment satisfaction scores following the switch to teriflunomide regardless of the reason for treating with teriflunomide [ 21 ]. Furthermore, real-world outcomes from the Danish Multiple Sclerosis Registry showed a favorable relapse-free and progression-free rate [ 22 ]. Finally, patient-related outcomes in our study showed a similar improvement concerning treatment satisfaction compared with previous surveys [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation